MOLECULAR EVALUATION OF CHLAMYDIA TRACHOMATIS AND NEISSERIA GONORRHOEAE INFECTIONS AND THEIR CO-INFECTION AMONG WOMEN WITH INFERTILITY ISSUES AT GYNEACOLOGICAL CLINICS IN ADO – EKITI, NIGERIA (Journal of Biomedical Investigation, 2025)
Background: Chlamydia trachomatis and Neisseria gonorrhoeae are obligate intracellular bacteria that cause urethritis, cervicitis, salpingitis, pelvic inflammatory disease, ectopic pregnancy, painful urination, abnormal and unusual increase discharge from the vagina and penis. Due to the similarities in these microorganisms’ clinical presentations, one can be taken for the other.Aim: This study evaluated the level of chlamydia and gonorrhoeae infections and their co-infection among women attending fertility clinics in Ado–Ekiti, Ekiti State.Methods: 115 urine and 115 high vagina swab samples (230 samples) were collected from women attending selected fertility clinics. Rapid kits specific for C. trachomatis and N. gonorrhoeae were used and quantitative polymerase chain reaction (qPCR) was carried out to further test for these microorganisms in both urine and high vagina swabs samples.Results: A total of 36 (31.3%) and 39 (33.9%) were positive to C. trachomatis and N. gonorrhoeae respectively when tested with rapid test kit using urine sample; 37 (32.2%) and 49 (42.6%) were positive to C. trachomatis and N. gonorrhoeae respectively when urine samples were tested with qPCR; 13 (11.3%) were positive C. trachomatis when HVS samples were tested with qPCR, 51 (44.3%) were positive to N. gonorrhoeae with HVS samples when tested with qPCR. A total of 19 (16.5%) showed co–infection of C. trachomatis and N. gonorrhoeae with rapid kit using urine; 23 (20%) showed co–infection of these microorganisms when tested with qPCR and 9 (7.8%) showed co–infection from HVS samples tested with qPCR. Co–infection of C. trachomatis and N. gonorrhoeae were statistically significant (p
Keywords: Infertility; C. trachomatis; N. gonorrhoeae; co–infection; women